PENGGUNAAN METODE OUTDOOR LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS ANAK USIA 5-6 TAHUN - Siti Annisa Aszari; Uswatul Hasni; Winda Sherly Utami (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study was motivated by initial observations at TK Al Ikhlas in Singkawang Village, Muara Bulian District, which revealed that the logical thinking abilities of children aged 5-6 years were still relatively low. The children appeared unable to logically sequence objects, arrange patterns, classify items based on color, shape, and size, or draw simple conclusions from their activities. The research employed a quantitative approach using a pre-experimental design in the form of a One Group Pretest-Posttest Design. The study involved 22 children selected through a saturated sampling technique. Data were collected using observation sheets, while data analysis included normality testing, homogeneity testing, and hypothesis testing. The results showed an increase in the average score from 12.77 (total score: 281) in the pre-test to 21 (total score: 462) in the post-test, with a mean difference of 8.23. The hypothesis test produced a t-value of 22.483, which exceeded the t-table value of 2.086 at a significance level of α = 0.05.  Therefore, the outdoor learning method had a significant effect on improving the logical thinking skills of children aged 5-6 years at TK Al Ikhlas and was proven to be an effective learning approach for stimulating cognitive development in early childhood education.